Control de la materia prima y su incidencia en los costos de producción de la caja de banano en la empresa Reybanpac, año 2009 - Peláez Mendoza, José Carlos (2010)
In the Degree Thesis “Control of the raw material and its incidence in the costs of production of the banana box in the company Reybanpac C.A. ”, the following objectives: to determine the procedures used to control the raw material; know the administrative structure proposed by Reybanpac C.A. for control of raw materials; establish the raw material that is outside the optimal parameters; determine the cost of raw material per box and based on the results propose the application of a raw material monitoring and control plan in the company Reybanpac C.A. To develop the research work, the administrative staff of Reybanpac C.A., comprised of inventory assistants, administrators, winemakers, process supervisors and heads of sectors. The sample of respondents was determined by applying the D'ONOFRE formula HORACIO, leaving as a respective sample 45 winemakers, 47 heads of sectors, 45 process supervisors, 42 administrators and 5 inventory assistants. The information resulting from the surveys was processed with the Excel application and then organized in graphs, for the respective analyzes. The information obtained from the key informants was discussed, in relation to to the nature of the hypothesis, determining that the inefficient management and application of the raw material affects the increase of $ 0.21 in the cost of the banana in the company Reybanpac C.A. In order to improve the control of the raw material, the present work research includes the proposal of a "Plan for Monitoring and control of the premium in Reybanpac C.A. ”, which is a basic tool to be able to organize both the inventory system and the raw material control procedures, proposing that the company can reduce its production costs through of a correct handling of the optimal consumption of materials.